The evolution of the bound particle reservoir in Wendelstein 7-X and its influence on plasma control. (17th February 2021) - Schlisio, G.; Wenzel, U.; Naujoks, D.; Pedersen, T.S.; Grote, H.; Winters, V.R.; Niemann, H.; Mulsow, M.; Krychowiak, M.; Drewelow, P.; Gao, Y.; Jakubowski, M.; et al.
Abstract: The investigation of fuel retention in fusion experiments is important in view of plasma density control as well as tritium inventory for future fusion reactors. We present a first gas balance of the stellarator Wendelstein 7-X with its inertially cooled graphite divertor. The gas balance is used to estimate the wall inventory and it is found that the wall plays an important and dynamic role, absorbing or releasing particles depending on the plasma conditions. Several different scenarios are presented and the effect of fueling and heating on the wall inventory is assessed. We find that the record duration plasma experiment of 100 s required previous shorter plasmas to be successfully conducted.